Αρετη w przekazach przedchrześcijańskich. Zarys zagadnienia - Zgraja, Brunon (Vox Patrum, 2010)
This article presents the development of the meaning of arete in the sources from Homer to Albinus (VIII B.C. - II A.D.), which, together with changes happening in the economical, social, political and cultural life of the ancient Greece, began to mean all that gives to a person or to a thing a special value: a bodilly one, a practical, moral and intellectual one. Moreover, the way leading to achievement of arete, as well as the values resulting from its possession, has been presented.